Case Report: A report on the countermeasures after the rupture of the scalp venous indwelling needle catheter in 12 cases - Zhong, Haiyan; Wang, Mengze; Gui, Yang; Yang, Lei; Zhao, Qianhao (Frontiers in Surgery, 2023)
As a substitute for a scalp needle, the intravenous indwelling needle is easy to operate and easy to use. it is not only conducive to the rescue of critically ill children, improves nursing efficiency, but also avoids pain caused by repeated venipuncture. However, cases of indwelling needle catheter breaking and remaining in scalp vessels are rarely reported. This study collected 12 cases of scalp vein indwelling needle rupture and retention in scalp vessels in our center from January 2012 to January 2022. It was found that there were 7 males and 5 females, with an average age of 19.17 ±8.96 months. The average length of the severed end was 15.00 ±1.54mm. In 8 cases, the catheter was broken during the haircut, and in 2 cases, the wall structure was damaged and broken after repeated folding of the catheter. In 2 cases, the children did not cooperate during extubation, the head twisted violently and the catheter was broken.5 cases tried to extract it by manipulation and hemostatic forceps, of which 4 cases were successful, and 1 case was successfully removed after the completion of three-dimensional computerized tomography (3D-CT) imaging positioning. The remaining 7 cases were removed by operation, and the success rate of the first operation was 100% in 4 cases who chose 3D-CT. The other 3 cases chose ordinary CT plain scan positioning, the success rate of the first operation was 66.6%, and one child was successfully removed after the second operation after the failure of the operation plus 3D-CT scan positioning. All the children were in stable condition after the operation and were discharged smoothly. When the broken catheter is relatively shallow and the scalp is not completely closed, we could choose the preliminary positioning of B-ultrasound or ordinary CT, and then try to remove it by manual squeezing combined with hemostatic forceps. However B-ultrasound and ordinary CT could not meet the requirements of accurate location, 3D-CT has a very important localization value for surgery, which can improve the success rate and help successfully remove the ruptured catheter.